2008
DOI: 10.1080/13685530802400995
|View full text |Cite
|
Sign up to set email alerts
|

Baldness, benign prostate hyperplasia, prostate cancer and androgen levels

Abstract: This prospective study with selected small group of patients showed that there is no difference of male pattern baldness in BPH and prostate cancer patients and also there is no correlation between pattern of baldness and serum androgen levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 16 publications
3
30
0
Order By: Relevance
“…Because of no correlation between AGA and serum testosterone, free testosterone and bioavailable testosterone levels [6], pathogenic basis of androgen is likely to be mediated through the intracellular signaling of hair follicle target cells. Here, we briefly describe intracellular androgen signaling pathway.…”
Section: Androgen Signaling Pathway In the Target Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of no correlation between AGA and serum testosterone, free testosterone and bioavailable testosterone levels [6], pathogenic basis of androgen is likely to be mediated through the intracellular signaling of hair follicle target cells. Here, we briefly describe intracellular androgen signaling pathway.…”
Section: Androgen Signaling Pathway In the Target Cellsmentioning
confidence: 99%
“…2). In 1942, Hamilton [3] first demonstrated that this process is mediated mainly by androgen from his clinical evidences; (1) eunuchoid and prepubertally castrated men show complete retention of scalp hairs, (2) men castrated between the age of 14 and 19 years show no or only slight hair loss, (3) adult men with AGA castrated between the age of 20 and 43 years show no further extention of hair loss, (4) baldness can be induced by testosterone administration in eunuchoid and castrated men with genetic predisposition of AGA, (5) discontinuation of testosterone administration prevents progression of baldness but its restart resumes hair loss in eunuchoid and castrated men, (6) hair loss Androgenetic alopecia 5a-Reductase Androgen receptor ARA55/Hic-5 TGF-b DKK-1 A B S T R A C T Androgenetic alopecia (AGA) is characterized by vellus transformation of scalp hairs, corresponding to hair follicle miniaturization during repeated hair cycles with shortened anagen phase. This phenomenon is mediated mainly by androgen.…”
Section: Introductionmentioning
confidence: 98%
“…Several previous studies have investigated whether androgenetic alopecia is associated with prostate cancer, with largely conflicting results. A number of studies have found no association between androgenetic alopecia and prostate cancer (9)(10)(11)15) or suggestive evidence of an increased risk of prostate cancer (12), others have found androgenetic alopecia to be associated with an increased risk of prostate cancer (13,14,18), whereas 2 recent studies have found androgenetic alopecia to be associated with a decreased risk of prostate cancer (16,17). While differences in sample size, study design, and exposure assessment might plausibly explain much of the inconsistency between studies, the direction of estimated associations has differed even among those studies that assessed androgenetic alopecia at specific reference ages using an adapted Hamilton-Norwood scale (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated whether there exists any association between androgenetic alopecia and risk of prostate cancer (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). While some studies suggest that androgenetic alopecia, especially when it occurs in younger men, might be a marker of increased risk of prostate cancer later in life (12,13,18), others have found that androgenetic alopecia is in fact associated with lower risk of prostate cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, existing results are not only controversial but also limited by small cohorts, nonstandardized definitions of LUTS, and lack of control of confounding variables. [19][20][21][22] The objective of this study was to evaluate the association of cardiovascular risk factors and male LUTS for the first time in a Latin American population. A secondary objective was to evaluate a possible association between LUTS and AGA by multivariate analysis on a large cohort.…”
mentioning
confidence: 99%